2013
DOI: 10.1017/s136898001300061x
|View full text |Cite
|
Sign up to set email alerts
|

The association of breakfast skipping and television viewing at breakfast with weight status among parents of 10–12-year-olds in eight European countries; the ENERGY (EuropeaN Energy balance Research to prevent excessive weight Gain among Youth) cross-sectional study

Abstract: Objective: The main objective was to assess the relationship of breakfast skipping, television (TV) viewing at breakfast and breakfast without TV with weight status among parents of 10-12-year-olds in eight European countries. Design: A cross-sectional survey assessed breakfast eating and TV viewing at breakfast by three frequency questions and parents were categorized into: (i) breakfast skippers; (ii) breakfast with TV (TV watchers at breakfast); and (iii) breakfast without TV (breakfast eaters who do not wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
1
21
2
2
Order By: Relevance
“…The foods and beverages consumed while watching television by children and adolescents who watch more than 2 hours per day have been found to be more energy dense than the foods consumed by children and adolescents who watch less television [42,4446]. In a study involving eight European countries, the authors found that those who ate breakfast while watching TV were more likely to be obese [47]. …”
Section: Discussionmentioning
confidence: 99%
“…The foods and beverages consumed while watching television by children and adolescents who watch more than 2 hours per day have been found to be more energy dense than the foods consumed by children and adolescents who watch less television [42,4446]. In a study involving eight European countries, the authors found that those who ate breakfast while watching TV were more likely to be obese [47]. …”
Section: Discussionmentioning
confidence: 99%
“…In the United States and Australia, studies have shown a significant association between breakfast skipping and overweight/obesity. 23 , 24 In Europe, several studies have demonstrated a positive association between usual breakfast consumption and healthy BMI. 25 , 26 In the MENA regions, Musaiger suggested breakfast skipping as a factor associated with obesity, probably because breakfast consumers are more likely to have better overall diet quality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is postulated that the satiating properties of food over the course of the day decline12 and, therefore, eating earlier in the day could promote greater satiety than eating later in the day. However, despite this common recommendation for weight control by both health professionals13 14 and the lay community,15 16 17 most of these recommendations are based on the findings of observational studies 1819 20 21 These concepts have potential for selection bias and confounding, because those individuals who eat breakfast might differ from those who do not in several ways, including socioeconomic status and the adoption of other health related behaviours such as the consumption of a healthy diet.…”
Section: Introductionmentioning
confidence: 99%